Smart Portal Application a Complete App for Student and Staff Management - Parthipan Vadivel (International Journal of Informatics and Communication Technology (IJ-ICT), 2016)
In this article I am introducing a new model of Attendance which is very compactable for and useful for attendance managementToday is the generation of “Smart class”, ”e-learning” “Videoconferencing” “social networking” “Skype” “Facebook” “Whatsapp”.All class activities are done and carried out in system and web, Wi-Fi. The main core idea of this paper is to convert these activities into our Smart phones as Applications. The Application is nothing but a mobile app that can be installed in any Smartphone and use it through Wi-Fi.